Laparoscopic Nephrectomy, Ex Vivo Partial Nephrectomy, and Autotransplantation for the Treatment of Complex Renal Masses - Jasmir Gopal Nayak; Joshua Koulack; Thomas Brian McGregor (Case Reports in Urology)
In the contemporary era of minimally invasive surgery, very few T1/T2 renal lesions are not amenable to nephron-sparing surgery. However, centrally located lesions continue to pose a clinical dilemma. We sought to describe our local experience with three cases of laparoscopic nephrectomy, ex vivo partial nephrectomy, and autotransplantation. Laparoscopic donor nephrectomy was performed followed by immediate renal cooling and perfusion with isotonic solution. Back-table partial nephrectomy, renorrhaphy, and autotransplantation were then performed. Mean warm ischemia (WIT) and cold ischemic times (CIT) were 2 and 39 minutes, respectively. Average blood loss was 267 mL. All patients preserved their renal function postoperatively. Final pathology confirmed pT1, clear cell renal cell carcinoma with negative margins in all. All are disease free at up to 39 months follow-up with stable renal function. In conclusion, the described approach remains a viable option for the treatment of complex renal masses preserving oncological control and renal function.